Decolonisation of the Malay World: A Museum Revisit (MINDEN Journal of History and Archaeology, 2025)
Most museums in Malaysia especially the Muzium Negara (National Museum) have been under the jurisdiction of different ministries, from the Ministry of Culture, Youth and Sports to the Ministry of Local Government and Environment, then later to the Ministry of Culture, Arts and Tourism with recent move to the Ministry of National Unity. However, the museums have never been under the Ministry of Education and not seen as academic institutions, but rather as tourist sites. Studies on Malaysian museums revolve around the management and promotional strategies under the tourism lens while the critical studies on the narrative of the Malay world history from the pre-colonial period to the colonial period and the fight for freedom have been minimal. The main objective of this exhibition text analysis and the critical curatorial observation is to explore the narrative in the Muzium Negara in terms of the fight against the colonisers to gain independence and the representation of the Islamic-Malay civilisation history throughout the museum. The analysis revealed that the narrative in Muzium Negara is a colonial narrative of a nation state and provide a very minimal narrative of the fight against colonialism. There is also a lack of representation of the Islamic-Malay civilisation despite having many Malay Muslim sultanates in the Federation of Malaysia to reflect aspects of the Islamic-Malay civilisation. The findings suggest that the national museums such as Muzium Negara should include a civilizational approach in the representation of Malaysia as a form of decolonisation.Keywords: museum, decolonisation, Malay-Islamic civilisation, representation